Hubungan antara Tingkat Kecemasan dengan Peningkatan Tekanan Darah pada Pasien Pra Operasi Virectomy - Mohamad suroto; Betie Febriana (STIKes Hamzar, 2026)
Anxiety is a common psychological response in preoperative patients, including those undergoing vitrectomy, and it can affect physiological conditions such as increased blood pressure. Unstable blood pressure before surgery may delay the procedure and influence the need for anesthetic drugs. This study aimed to determine the relationship between anxiety levels and increased blood pressure in preoperative vitrectomy patients at the Baitul Ma’ruf inpatient ward of Sultan Agung Islamic Hospital Semarang. This research employed a quantitative design with a cross-sectional approach involving 100 respondents selected through total sampling during July–August 2025. Anxiety levels were measured using the Zung Self Rating Anxiety Scale, while blood pressure was measured using a calibrated digital sphygmomanometer at 24 hours and 3 hours before surgery. Data were analyzed using Spearman’s Rank correlation test. The results showed that most respondents experienced mild anxiety (65%) and mild increases in blood pressure (77%), with a p-value < 0.001 and a correlation coefficient of 0.574, indicating a significant relationship with moderate correlation strength. It can be concluded that anxiety is significantly associated with increased blood pressure in preoperative vitrectomy patients, highlighting the importance of nursing interventions to manage preoperative anxiety in order to stabilize blood pressure and prevent complications or surgical delays.